A Novel Ratiometric Probe Based on Nitrogen-Doped Carbon Dots and Rhodamine B Isothiocyanate for Detection of Fe3+ in Aqueous Solution. (16th March 2016) - Liu, Lin; Chen, Lu; Liang, Jiangong; Liu, Lingzhi; Han, Heyou
Abstract : A ratiometric probe for determining ferric ions (Fe 3+ ) was developed based on nitrogen-doped carbon dots (CDs) and rhodamine B isothiocyanate (RhB), which was then applied to selective detection of Fe 3+ in PB buffer solution, lake water, and tap water. In the sensing system, FePO4 particles deposit on the surface of CDs, resulting in larger particles and surface passivation. The fluorescence (FL) intensity and the light scattering (LS) intensity of CDs can be gradually enhanced with the addition of Fe 3+, while the FL intensity of RhB remains constant. The ratiometric light intensity of CDs LS and RhB FL was quantitatively in response to Fe 3+ concentrations in a dynamic range of 0.01–1.2  μ M, with a detection limit as low as 6 nM. Other metal ions, such as Fe 2+, Al 3+, K +, Ca 2+, and Co 2+, had no significant interference on the determination of Fe 3+ . Compared with traditional probes based on single-signal probe for Fe 3+ detection, this dual-signal-based ratiometric probe exhibits a more reliable and stable response on target concentration and is characterized by easy operation in a simple fluorescence spectrophotometer.